/ Therapeutic Phlebotomy Incidence in Patients with Polycythemia "Vera" Diagnosed by Hematocrit and Hemoglobin in the Blood Bank. "Riobamba" - Hidalgo Cajo, Byron Geovanny; Tinajero Novillo, Libia Cristina; Gualberto Mayacela, Angel; Choca Alcoser, Edwin Gilberto; Hidalgo Cajo, Ivan Mesias; Tinajero Novillo, Maria Alejandra (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2016)
Polycythemia is an increase in the total volume of red blood cells in blood, in effect hematocrit levels above 52% (men) or 48% (women) concentration greater than 18.5 g / dl (men) and 16.5 g / dl (women) demonstrate the presence of this myeloproliferative neoplasm which has high morbidity. The research was conducted with 172 patients, 141 men and 31 women. Phlebotomy is a method used to reduce high blood viscosity, and through which is drawn weekly 1 unit (500 cc) of blood until the hematocrit is 45%. To 62% of patients with phlebotomy compensation saline was performed, a remarkable improvement with therapeutic phlebotomy treatment is noticed; and, it was noted that no complications or side effects from successive bleeds, is a timely treatment, and effective.